2018
DOI: 10.1016/j.stem.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory Signaling in Tet2 Mutant Preleukemic Cells Mitigates Stress-Induced Abnormalities and Clonal Hematopoiesis

Abstract: SUMMARY Inflammation is a risk factor for cancer development. Individuals with preleukemic TET2 mutations manifest clonal hematopoiesis and are at a higher risk of developing leukemia. How inflammatory signals influence the survival of preleukemic hematopoietic stem and progenitor cells (preleukemic-HSPCs) is unclear. We show a rapid increase in the frequency and absolute number of Tet2-KO mature myeloid cells and HSPCs in response to inflammatory stress, which results in enhanced production of inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
238
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(273 citation statements)
references
References 65 publications
17
238
1
1
Order By: Relevance
“…While we have identified a stem cell intrinsic mechanism by which mutant p53 drives clonal hematopoiesis, recent studies indicate that mutations identified in CHIP may utilize cell extrinsic mechanisms to promote clonal hematopoiesis 5152 . For example, mutant hematopoietic cells displayed increased secretion of pro-inflammatory cytokines such as IL-1β and IL-6 5152 . Since some inflammatory response genes are upregulated in p53 mutant HSPCs (data not shown), we will investigate the cell extrinsic mechanisms by which mutant p53 drives CHIP in the future.…”
Section: Discussionmentioning
confidence: 85%
“…While we have identified a stem cell intrinsic mechanism by which mutant p53 drives clonal hematopoiesis, recent studies indicate that mutations identified in CHIP may utilize cell extrinsic mechanisms to promote clonal hematopoiesis 5152 . For example, mutant hematopoietic cells displayed increased secretion of pro-inflammatory cytokines such as IL-1β and IL-6 5152 . Since some inflammatory response genes are upregulated in p53 mutant HSPCs (data not shown), we will investigate the cell extrinsic mechanisms by which mutant p53 drives CHIP in the future.…”
Section: Discussionmentioning
confidence: 85%
“…51 On a functional level, reduced TET2 expression leads to clonal expansion of HSCs, [52][53][54] particularly in response to inflammatory stress. 55 ASXL1, another recurrently mutated gene in CH, also encodes a protein linked to epigenetic modification. Unlike DNMT3A and TET2 that directly modify DNA, ASXL1 is part of the so-called polycomb-group complex, which regulates transcription via histone modification.…”
Section: Functional Implications Of Recurrent Gene Mutations In Chmentioning
confidence: 99%
“…There is growing evidence of context-specific expansion of oncogenically-initiated hematopoietic progenitors: BCR-ABL or Ppm1d-deficiency with chemotherapy (Bilousova et al, 2005;Hsu et al, 2018;Kahn et al, 2018); Notch activation, Tp53-deficiency, or Cebpa-deficiency following γ-irradiation (Bondar and Medzhitov, 2010;Fleenor et al, 2015b;Marusyk et al, 2009;Marusyk et al, 2010); BCR-ABL, Myc, NRas V12 , or AML1-ETO in aging (Henry et al, 2015;Henry et al, 2010;Vas et al, 2012); and Jak V617F with TNF-α exposure (Fleischman et al, 2011) or Tet2-knockout with LPS challenge (Cai et al, 2018). Here, we show that chronic IL-1β is sufficient to drive selective expansion of Cebpa-deficient MPPs, directly connecting an inflammatory signaling pathway to a transcriptional fate network.…”
Section: Strikingly Chronic Il-1β Exposure Triggered a Fitness Advanmentioning
confidence: 99%